Design of digital electricity meter - Al-Khateeb, Khalid A. Saeed (2010)
Common Electricity meters, which are currently used in houses, shops and some factories are bulky expensive and inaccurate. Such features are incompatible with modern technological trends of miniaturization accuracy and neat devices. This project presents the design and the model of a low cost digital energy meter to overcome the short comings of the present meters. It is anticipated that a new neat design based on integrated circuit technology employing digital measurement techniques will have a great impact on electricity meters locally and worldwide. With a data storage capability and some form of processing, it can provide the consumers with vital information on the trend of their energy consumption. Such information will assist them in rationalizing their consumption. Intelligent energy meters may be seen as most suitable and efficient way to facilitate easy solutions to the problem of rational consumption.